2010
DOI: 10.1038/ni.1840
|View full text |Cite
|
Sign up to set email alerts
|

Signaling by intrathymic cytokines, not T cell antigen receptors, specifies CD8 lineage choice and promotes the differentiation of cytotoxic-lineage T cells

Abstract: Immature CD4+CD8+ (double-positive (DP)) thymocytes are signaled via T cell antigen receptors (TCRs) to undergo positive selection and become responsive to intrathymic cytokines such as interleukin 7 (IL-7). We report here that cytokine signaling is required for positively selected thymocytes to express the transcription factor Runx3, specify CD8 lineage choice and differentiate into cytotoxic-lineage T cells. In DP thymocytes genetically engineered to be cytokine responsive, IL-7 signaling induced TCR-unsigna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
235
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,785 publications
(246 citation statements)
references
References 50 publications
7
235
0
Order By: Relevance
“…Park et al (45) recently showed that RUNX3 is induced by common ␥ chain (␥c) receptor signaling during CD8 T specification. The process is dependent on STAT5 or STAT6 as ␥c-related cytokine stimulation of thymocytes from Stat5/6 double knock-out mouse did not induce Runx3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al (45) recently showed that RUNX3 is induced by common ␥ chain (␥c) receptor signaling during CD8 T specification. The process is dependent on STAT5 or STAT6 as ␥c-related cytokine stimulation of thymocytes from Stat5/6 double knock-out mouse did not induce Runx3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…During positive selection, class II recognition is thought to induce strong persistent signaling that results in a cascade of transcriptional regulation by factors such as GATA3 and T-helper-inducing POZ/Krüppel-like factor, which results in fixation of cells to the CD4 lineage (3,4). In contrast, weaker or transient signaling by class I MHC results in the cytokine-dependent induction of a Runx3-mediated transcriptional program that induces CD8 lineage commitment (5)(6)(7)(8).…”
Section: Cd4 T Cells | Cd8 T Cellsmentioning
confidence: 99%
“…47 The preferential expansion of CD8 + reverted T cells makes our X-SCID case unique and suggests a more important role for CD132-signaling in proliferation (homeostatic or antigen-driven) of CD8 + T cells as compared to CD4 + T cells. 48 The IL2RG gene reversion in the polyclonal CD8 + T-cell outgrowth did not result in complete recovery of all clinical symptoms demonstrating that rescue of CD8 + T cells alone is not sufficient for full restoration of immunity. …”
mentioning
confidence: 99%